Kepemimpinan Transformasional Kepala Sekolah dan Budaya Kolaboratif sebagai Pengungkit Kinerja Guru: Tinjauan Konseptual dalam Manajemen Pendidikan: Principal Transformational Leadership and Collaborative Culture as Leverage for Teacher Performance: A Conceptual Review in Educational Management - Celine Yinnie; Farida Yuliaty (ITScience (Information Technology and Science), 2026)
Teacher performance is a strategic factor in determining educational quality, influenced not only by individual competency but also by the principal's leadership and the work culture that develops within the school environment. This article aims to conceptually examine the roles of the principal's transformational leadership and collaborative culture as levers for teacher performance within educational management. The method used is a narrative literature review that examines various sources, including books and scholarly articles, relevant to leadership, organizational culture, and teacher performance. The analysis was conducted by identifying, classifying, and synthesizing concepts to build a comprehensive understanding framework. The study's results indicate that transformational leadership plays a crucial role through the principal's ability to establish a clear vision, serve as a role model, motivate, stimulate intellectual growth, and provide individual attention to teachers. Conversely, a collaborative culture strengthens professional interactions through knowledge sharing, problem-solving discussions, and continuous collective learning. The synergy between transformational leadership and a collaborative culture can create a conducive work climate, increase commitment, and encourage teachers to work more effectively, reflectively, adaptively, and innovatively. The implications of this study emphasize that principals need to act as agents of change, focusing not only on administrative aspects but also on strengthening a participatory and sustainable collaborative work culture. Thus, improved teacher performance can be achieved through the integration of visionary leadership and a supportive work environment.